Perioperative risk factors for delayed extubation after acute type A aortic dissection surgery - Maisat, Wiriya (J Thorac Dis, 2020)
BACKGROUND: Delayed extubation after cardiac surgery is associated with high morbidity and mortality, increased intensive care unit length of stay, and healthcare cost. Acute type A aortic dissection (ATAAD) generally results in prolonged mechanical ventilation due to the complexity of surgical management and some postoperative complications. This study aimed to elucidate the perioperative risk factors for delayed extubation in patients undergoing ATAAD surgery. METHODS: A retrospective cohort study including 239 patients who were diagnosed with ATAAD and underwent emergency surgery from October 2004 to January 2018 was performed. The potential perioperative risk factors for delayed extubation were collected. This study defined delayed extubation as the time to commence extubation being greater than 48 hours. The clinical data were analyzed with univariate and multivariate analyses to identify risk factors for delayed extubation following ATAAD surgery. RESULTS: The incidence of delayed extubation was 48.5% (n=116). Multiple logistic regression analysis showed perioperative risk factors for delayed extubation included preoperative cardiac tamponade [odds ratio (OR) 3.94, 95% confidence interval (CI) 1.39–11.17, P=0.010], central arterial cannulation (ascending aorta and proximal aortic arch) for cardiopulmonary bypass (CPB) (OR 4.04, 95% CI: 1.03–15.91, P=0.046), postoperative stroke (OR 10.58, 95% CI: 2.65–42.25, P=0.001), postoperative renal dysfunction that required temporary hemodialysis (OR 6.60 95% CI: 1.97–22.11, P=0.002), and re-exploration to stop bleeding (OR 2.65, 95% CI: 1.00–6.99, P=0.050). CONCLUSIONS: Preoperative cardiac tamponade, central arterial cannulation for CPB, postoperative stroke, postoperative renal dysfunction that required temporary hemodialysis, and re-exploration to stop bleeding are perioperative risk factors for delayed extubation. Identification of the potential risk factors for delayed extubation may help optimize the perioperative management and improve postoperative outcomes of patients undergoing ATAAD surgery.